2000
DOI: 10.1016/s0893-133x(99)00157-8
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Primary and Secondary Reward-Relevant Limbic Nuclei in an Animal Model of Relapse

Abstract: The neural substrates underlying relapse to drug-seeking behavior after chronic drug abuse may differ from those underlying immediate drug-taking behavior. In a model of relapse to drug-seeking behavior following chronic cocaine self-administration and prolonged extinction, we have previously shown that rats will significantly reinstate lever responding for either primary reward (cocaine) or secondary reward (tone + light stimulus previously paired with cocaine). In the present study, we utilized reversible in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
164
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(182 citation statements)
references
References 36 publications
16
164
2
Order By: Relevance
“…The voltage-dependent sodium channel blocker TTX, an agent that temporarily inhibits impulse generation and neural conductance (Narahashi, 1972), has been utilized as a reversible neural inactivating agent in numerous behavioral studies (eg Fuchs et al, 2005Fuchs et al, , 2006Grimm and See, 2000;Harlan et al, 1983). In the current study, TTX was not directly administered into the CA1 region of the hippocampus, which would have ruled out a direct role of the CA1 in the acquisition of cocaine-seeking.…”
Section: Discussionmentioning
confidence: 99%
“…The voltage-dependent sodium channel blocker TTX, an agent that temporarily inhibits impulse generation and neural conductance (Narahashi, 1972), has been utilized as a reversible neural inactivating agent in numerous behavioral studies (eg Fuchs et al, 2005Fuchs et al, , 2006Grimm and See, 2000;Harlan et al, 1983). In the current study, TTX was not directly administered into the CA1 region of the hippocampus, which would have ruled out a direct role of the CA1 in the acquisition of cocaine-seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ERKs have been shown to be activated in the central amygdala (CeA) after cue-induced relapse to cocaine seeking and inhibition of ERKs in the CeA decreased cocaine seeking after drug withdrawal (Lu et al, 2005). All these observations suggest that molecular alterations in the amygdala may be involved in cue-induced relapse to drug seeking (Grimm and See, 2000;Yun and Fields, 2003). However, the activation of transcription factors and signaling cascades in the amygdala has never been analyzed in detail in animal models of relapse to alcohol seeking.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one early report identified that the basolateral region of the amygdala as being critical for the reinstatement response to conditioned stimuli (CS) priming [19]. Subsequently, Grimm & See [13] demonstrated that inactivation of the nucleus accumbens was effective in preventing drug (cocaine) induced drug seeking, but had no effect on CS induced priming of reinstatement. The opposite relationship was found to exist for inactivation of the basolateral amygdala, as tetrodotoxin infusion did not affect drug primed reinstatement.…”
Section: Introductionmentioning
confidence: 99%